2016
DOI: 10.1161/jaha.116.004496
|View full text |Cite
|
Sign up to set email alerts
|

Common Variant in Glycoprotein Ia Increases Long‐Term Adverse Events Risk After Coronary Artery Bypass Graft Surgery

Abstract: BackgroundThis study was aimed to investigate the clinical relevance between glycoprotein Ia (GPIA) rs1126643C/T polymorphism and the outcome of coronary artery disease after coronary artery bypass graft (CABG) surgery and explore the involved potential mechanisms.Methods and ResultsWe genotyped GPIA rs1126643 polymorphism of 1592 patients who underwent CABG and followed up for a median period of 72.8 months. Patients who are GPIA rs1126643 T‐allele carriers have a higher major adverse cardiac or cerebrovascul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
(58 reference statements)
0
4
0
Order By: Relevance
“…Preventing recurrent cardiovascular events in patients who underwent CABG is a signi cant challenge [22]. The previous study reported that the incidence of 5-year MACE in individuals with post-CABG is around 11.8% to 31.0% [23], indicating early identi cation of patients prone to MACE after having CABG is essential. However, most previous studies focused on the effect of traditional risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Preventing recurrent cardiovascular events in patients who underwent CABG is a signi cant challenge [22]. The previous study reported that the incidence of 5-year MACE in individuals with post-CABG is around 11.8% to 31.0% [23], indicating early identi cation of patients prone to MACE after having CABG is essential. However, most previous studies focused on the effect of traditional risk factors.…”
Section: Discussionmentioning
confidence: 99%
“…Preventing recurrent cardiovascular events in patients who underwent CABG is a significant challenge [ 24 ]. The previous study reported that the incidence of 5-year MACE in individuals with post-CABG is around 11.8 to 31.0% [ 25 ], indicating that early identification of patients prone to MACE after having CABG is essential. However, most previous studies focused on the effect of traditional risk factors [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The patient collective in this study suffered to a large extent of 3-vessel disease (88%) and several cardiovascular risk factors (hypertension 67%, hyperlipidemia 68%, and diabetes mellitus 33%), which predestines them for future cardiovascular events. Patients with hypertension showed a significantly increased rate of major adverse cardiovascular events when compared to patients without hypertension ( 29 ). Heeschen et al have previously shown that elevated levels of soluble CD40 ligand (sCD40L), which is released after platelet activation, are associated with increased risk of cardiovascular events in patients with CAD ( 30 ).…”
Section: Discussionmentioning
confidence: 99%